2016
DOI: 10.1177/1470320316664611
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lycopene on modulation of renal antioxidant enzymes, ACE and ACE gene expression in hyperlipidaemic rats

Abstract: Introduction:We aimed to evaluate the efficacy of lycopene on renal tissue antioxidant enzymes and angiotensin converting enzyme (ACE) gene expression and serum activity in diet-induced hyperlipidaemia.Methods:Thirty-two female Wistar albino rats (200–250 g weight), 5–6 months of age, were randomly selected and divided into four groups. Group I received normal diet; group II received 24 g high fat diet/100 g of daily diet; group III received 24 g high fat diet/100 g daily diet and 200 ml of lycopene extract (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Lycopene has antihypertensive effects due to inhibition of the angiotensin converting enzyme (ACE) and due to its antioxidant effect, reducing oxidative stress induced by angiotensin-II and indirectly enhancing production of nitric oxide in the endothelium (Li and Xu, 2013 ; Belovic et al, 2016 ; Khan et al, 2016 ; Han and Liu, 2017 ). A study including 8,556 adult overweight and obese participants demonstrated association of lycopene and lycopene/uric acid ratio with lower prevalence of hypertension (Han and Liu, 2017 ).…”
Section: Cardiovascular Protective Mechanismsmentioning
confidence: 99%
“…Lycopene has antihypertensive effects due to inhibition of the angiotensin converting enzyme (ACE) and due to its antioxidant effect, reducing oxidative stress induced by angiotensin-II and indirectly enhancing production of nitric oxide in the endothelium (Li and Xu, 2013 ; Belovic et al, 2016 ; Khan et al, 2016 ; Han and Liu, 2017 ). A study including 8,556 adult overweight and obese participants demonstrated association of lycopene and lycopene/uric acid ratio with lower prevalence of hypertension (Han and Liu, 2017 ).…”
Section: Cardiovascular Protective Mechanismsmentioning
confidence: 99%
“…An increase in intracellular GSH content under the effect of Lyc (lower concentrations) ( Fig. 5B) is not an unexpected finding, since the application of Lyc to healthy animals also caused an increase in this nonenzymatic antioxidant level in kidney (Khan et al 2016). When the MTX was applied to cells, an increase in GSH concentration could be connected to its involvement in ROS detoxication (Dhanesha et al 2015) as well as to its usage for MTX transport inside the cell (Leszczyń ska and Pfaff 1982).…”
Section: Discussionmentioning
confidence: 78%
“…Introducing a healthy lifestyle may seem to be an effective method in the prevention and treatment of arterial hypertension [103]. Many studies show that healthy eating habits, and especially high dietary intake of fruit and vegetables and supplements with antioxidant properties, are able to guarantee the improvement of vascular function and BP [104]. Due to this, supplementation with bioactive food ingredients, such as lycopene, in the control of arterial hypertension is important in this case.…”
Section: Hypertension and The Effect Of Lycopenementioning
confidence: 99%